Complete genome sequence data of Xylella fastidiosa subspecies multiplex ST88 and ST89 indicate distinct introductions in FranceNCBINCBI - Amandine Cunty; Jessica Dittmer; Déborah Merda; Bruno Legendre; Benoit Remenant; Yannick Blanchard; Sophie Cesbron; Marie-Agnès Jacques; Pascal Gentit; Anne-Laure Boutigny (Data in Brief, 2025)
Xylella fastidiosa is a Gram-negative bacterium native to the Americas and classified as a priority pest under EU regulations. This xylem-limited plant pathogenic bacterium has a wide host range and is transmitted by insect vectors. Since 2013, X. fastidiosa has been identified in several European countries including Italy, France, Spain and Portugal, with different subspecies and sequence types (ST) detected. Since 2015, most strains identified in France are of the subspecies multiplex, specifically ST6 and ST7. Two new STs of X. fastidiosa subsp. multiplex, ST88 and ST89, were recently detected in the region Provence-Alpes-Côte d’Azur (PACA), and one strain of each ST has been isolated from infected plants. To investigate the phylogenetic relationships between the four STs present in France, a complete circular genome and a single-contig genome were assembled for the ST89 and ST88 strains, respectively, by combining PacBio and Illumina sequencing data. A phylogenomic analysis was performed to investigate the phylogenetic position and potential origin of these new strains. This data article contributes to improve our knowledge of the diversity and origin of X. fastidiosa subsp. multiplex in France and Europe.